Analisis Ketimpangan Pendapatan Kabupaten/Kota di Kawasan Kedungsepur Provinsi Jawa Tengah - Annis Nurfitriana Nihayah,; Dwi Rahmayani,; Grace Natalia Marpaung,; Rahmadani Nur Permanawati,; Ayuntavia, (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Kedungsepur is a Particular Region which is included in the National Spatial Planning. This region purpose to in an integrated manner equitable income disparities and increase the economic growth. In encouraging the region development optimally, it is needed the solid relationship interregion (districts/cities) in Kedungsepur Region. In practice the cooperation is less work effectively because of the unbalanced economic growth. This study aimed to analyse the effect of education, health, primary sector, secondary sector and tertiary sector on income disparity districts/cities in Kedungsepur Region Central Java Province. This study method using indeks Williamson and regression analysis panel data model (cross section and time series) with Fixed Effect Model. The data used in this research is secondary data obtained from the Central Statistics Agency (BPS) of Central Java Province and object of this research is district/cities in Kedungsepur Region Central Java Province. The result were obtained average indeks Williamson during 2015-2024 include low is 0,11. And regression of education variables, secondary sector and tertiary sector influenced positively on income disparity districts/cities in Kedungsepur Region Central Java Province. Whereas the variables health and primary sector influenced negatively on income disparity districts/cities in Kedungsepur Region Central Java Province.